Progress in palliative care in Israel: comparative mapping and next steps - Bentur Netta; Emanuel Linda L; Cherney Nathan (BMC, 2012)
Abstract Palliative care was established rapidly in some countries, while in other countries its establishment has taken a different trajectory. This paper identifies core steps in developing a medical specialty and examines those taken by Israel as compared with the US and England for palliative care. It considers the next steps Israel may take. Palliative care aims to provide quality of life for those with serious illnesses by attending to the illness-prompted physical, mental, social, and spiritual needs of patients and their families. It has ancient roots in medicine; its modern iteration began against the backdrop of new cures and life-sustaining technology which challenged conceptions of how to respect the sanctity of life. The first modern hospice was created by Saunders; it provided proof that palliative care works, and this has occurred in Israel as well (the first step). Another key step is usually skills development among clinicians; in Israel, few education and training opportunities exist so far. Specialty recognition also has not yet occurred in Israel. Service development remains limited and a major shortage of services exists, compared to the US. Research capacity in Israel is also limited. Policy to develop and sustain palliative care in Israel is underway; in 2009, the Ministry of Health established policy for implementing palliative care. However, it still lacks a financially viable infrastructure. We conclude that palliative care in Israel is emerging but has far to go. Adequate resource allocation, educational guidelines, credentialed manpower and specialty leadership are the key factors that palliative care development in Israel needs.